TI_GERICHTE 52.2005.280 vom 19. Oktober 2005 , Costruzione casa d'abitazione unifamiliare nella zona nucleo - TI Tribunale d'appello (2005)
Costruzione casa d'abitazione unifamiliare nella zona nucleo